HUBUNGAN TINGKAT DEPRESI DENGAN TERJADINYA INSOMNIA PADA LANSIA USIA 60-70 TAHUN DI DESA MAYANGGENENG KECAMATAN KALITIDU KABUPATEN BOJONEGORO - SYA'DIAH, SITI NURUL (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
Depression is one of the cause of  insomnia occurrence in aging people depression can cause someone to become sorrowful, sleepless and feels exhausted whenThe purpose of  this research is to analyze the correlation between  depression level with  insomnia occurrence aging peolpe  in Desa Mayanggeneng Kecamatan Kalitidu Kabupaten Bojonegoro. Analytic method applied is by using  cross sectional approach with population consists of 60 - 70 year old people in Desa Mayanggeneng Kec. Kalitidu Kab. Bojonegoro. Purpose sampling is used, there are 50 respondents this research is using two variables : depression as the independent variable  insomnia  in aging people as dependent variable. The data is collected by using questionaire sheet and  analyzed by with  spearman Rho test.Result of this research shows that light depression 23 responders ( 46%), 18 responders ( 36%) were not depressed, 7 responders were medium depressed  ( 14%) and 2 responder ( 4%) are heavy depressed.There are 28 respondents who experienced insomnia (56%) and 22 respondents who didn?t experience insomnia (44%). Result of statistical test  spearman rho  is 0,002 having value significant is meaning there is correlation between depression with insomnia in aging people.Result of this research shows that there is correlation between depression with insomnia in aging people. The prevention of depression in aging people is expected to protect them from the risk of insomnia.   Keyword : depression, insomnia, aging people